2021
DOI: 10.1371/journal.pone.0255873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical distancing policy on reducing transmission of SARS-CoV-2 globally: Perspective from government’s response and residents’ compliance

Abstract: Background COVID-19 was declared a public health emergency by the World Health Organization (WHO) in January 2020. Various physical distancing interventions were introduced to flatten the epidemic curve and reduce the disease burden. We evaluated the impacts of policy stringency and residents’ compliance on time-varying reproduction number in 17 countries. Methods Data were from WHO reports of local transmission (February 28 to April 8, 2020) in Australia, Canada, Finland, France, Germany, Greece, Italy, Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…* p < 0.05. pollution. The 7-day lag effect on the newly confirmed COVID-19 cases and mortality was reported in previous studies (Wang et al, 2020a;Chung and Chan, 2021;Dales et al, 2021). Previous findings showed that 10 µg m -3 increase in PM 2.5 was associated with the confirmed cases of COVID-19, and the estimated strongest relative risk were observed at 7-day lag (Wang et al, 2020a).…”
Section: Air Pollution Was Associated With Increases In Confirmed Covid-19 Casessupporting
confidence: 65%
“…* p < 0.05. pollution. The 7-day lag effect on the newly confirmed COVID-19 cases and mortality was reported in previous studies (Wang et al, 2020a;Chung and Chan, 2021;Dales et al, 2021). Previous findings showed that 10 µg m -3 increase in PM 2.5 was associated with the confirmed cases of COVID-19, and the estimated strongest relative risk were observed at 7-day lag (Wang et al, 2020a).…”
Section: Air Pollution Was Associated With Increases In Confirmed Covid-19 Casessupporting
confidence: 65%
“…Declared a global pandemic in March 2020, the outbreak of COVID-19 caused by the novel coronavirus SARS-CoV-2 in early 2020 brought about major changes to human dynamics on a global scale 4 . Governments restricted people’s mobility through stay at home requirements termed “lockdowns” 5 to prevent the spread of disease 6 .…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the community’s level of compliance is essential, whether the compliance is towards preventive measures for healthy individuals or towards isolation instructions for the infected individuals. In addition, social gatherings and non-complying to physical distancing would increase COVID-19 transmission [50] , [51] . Moreover, social behaviors in small or mass gatherings play an important role in managing the rate of transmission.…”
Section: Application Of Haddon Matrix To Covid-19 Transmission and Severitymentioning
confidence: 99%